Enhancing Creative Skills in Students through Color and Composition Lessons in Fine Arts - Abdurahmonova Dildora Nizomjon qizi (NEW SCIENTIFIC PERSPECTIVES AT THE INTERSECTION OF LANGUAGE, CULTURE, AND TECHNOLOGY, 2025)
Abstract: This article explores effective pedagogical methods for teaching color and composition in fine arts classes, aimed at enhancing students’ creative thinking, aesthetic literacy, and visual perception. Emphasis is placed on interactive activities, project-based learning, and differentiated instruction as strategies to engage students of diverse abilities and learning styles. The study highlights how structured practical exercises and collaborative projects foster both technical skills and independent artistic expression, preparing students for advanced artistic learning.